2016
DOI: 10.1177/1602400220
|View full text |Cite
|
Sign up to set email alerts
|

Bioceramic Bone Graft Substitute for Treatment of Unicameral Bone Cysts

Abstract: A single percutaneous injection of the bioceramic for UBC achieved good functional and radiological outcome while avoiding donor-site morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, due to the introduction of CP, the mechanical strength of the composite is superior to CS and autogenous cancellous bone (17). Both animal studies and clinical studies have demonstrated the satisfactory osteogenesis and antibiotic loading effect of CS/CP composites (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to the introduction of CP, the mechanical strength of the composite is superior to CS and autogenous cancellous bone (17). Both animal studies and clinical studies have demonstrated the satisfactory osteogenesis and antibiotic loading effect of CS/CP composites (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The value in our approach of combining vancomycinloaded CS/CP with autologous cancellous bone in induced membrane technology is that it overcomes limited sources of autogenous cancellous bone, thus enabling local antibiotic delivery and enhancing mechanical strength. Although CS/CP has been applied in various clinical fields like the treatment of necrosis of the femoral head, bone cysts, and bone tumors, no studies have analyzed the clinical effect of the induced membrane technique associated with CS/CP as an autologous bone graft expander in the treatment of large infected bone defects (18,19,21).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results of using autologous grafting in simple bone cysts are still poor, possibly due to excessive resorption [2,5,9,20,27]. Calcium sulphate (CaSO 4 ) and calcium phosphate (CaPO 4 ) are osteoconductive, biodegradable, and percutaneously injectable, particularly in the paediatric population [28]. Tey exhibit diferent resorption, mechanical, and side efect profles; calcium sulphate is more acidic and dissolves quicker, resulting in a higher frequency of long-term drainage and subsequent wound complications, whilst calcium phosphate maintains its architecture for a longer duration but has been associated with adverse and sometimes painful soft tissue reactions [29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Tey exhibit diferent resorption, mechanical, and side efect profles; calcium sulphate is more acidic and dissolves quicker, resulting in a higher frequency of long-term drainage and subsequent wound complications, whilst calcium phosphate maintains its architecture for a longer duration but has been associated with adverse and sometimes painful soft tissue reactions [29][30][31][32][33][34]. Composites have been developed to improve compressive strength and generate intermediate resorption [10,28].…”
Section: Discussionmentioning
confidence: 99%
“…The CaP materials are used to treat bone cysts [ 8 ] caused by an oncotomy in particular. The key problem is to overcome the minimal residual disease and to kill malignant mesenchymal or leukemic cells in the highly vascularized bone and red marrow (RM) areas [ 9 ].…”
Section: Introductionmentioning
confidence: 99%